IMPACT OF CARBON TAXES ON COMPANY FINANCE - Euriver Zega; Merwati Waruwu; Ningsih; Muammar Khaddafi (Universitas Efarina, 2023)
Carbon tax is new matter for company in Indonesia nowadays. The tax that charges for carbon is embodiment of constitution commitment. Indonesia government make a promise that written in Indonesia Constitution, which is the promise is to provide all of Indonesian People and give everyone healthy living environment. This promise has evolved into a carbon tax which is expected to curb corporate carbon spreading. This study will be based on Indonesia law Number 7 of 2021 on the Harmonization of Tax Regulation and Presidential Regulation Number 98 of 2021 on the Implementation of Carbon Value.